PENYAJIAN LAPORAN KEUANGAN PENGELOAAN DANA HAJI: GAGASAN YANG DAPAT DIPAHAMI PEMANGKU KEPENTINGAN - Yogashwara Vidyan; Rafidah Rafidah (FINANSIA : Jurnal Akuntansi dan Perbankan Syariah, 2023)
Hajj funds managed by BPKH need to pay attention to pilgrims' attention and sufficient accountability. Financial statements of Hajj financial management often get various criticisms from the public for the way of presentation and understanding that occurs in the community in reading the financial statements of Hajj funds. The research conducted is qualitative, then reviews the literature on the presentation of financial statements of similar entities. The unification of Hajj fund management reports with BPKH financial statements has been regulated in the Law of the Republic of Indonesia Number 34 of 2014 concerning Hajj Financial Management. There needs to be an easy-to-understand idea of transparency, accountability, and adequate understanding for the public to understand the Hajj fund report, namely by separating the Hajj fund management report from BPKH's financial statements as benchmarked in other fund management institutions.